Formulation of the Marketing Strategy for Viriya Crispy Fish SMEs Using the STP and 4P Approaches within the Indonesian National Police (Polri) Environment - Wiriyani, Kadek; Lahindah, Laura (Journal Research of Social Science, Economics, and Management, 2024)
This study aims to analyze the application of the STP and 4P marketing strategies in the context of MSMEs, focusing on Viriya Crispy Fish, a snack made from anchovies that is primarily targeted at members of the Indonesian National Police (Polri). This product is tailored to meet the needs of Polri personnel who require convenient and nutritious snacks, especially those working in the field. The study employs a qualitative approach, analyzing both the enabling and constraining factors involved in the implementation of Viriya Crispy Fish’s marketing strategy. Data is gathered through interviews and a review of relevant literature on MSME marketing. The results indicate that Polri’s support, which includes entrepreneurial training, business legality assistance, and facilitation of access to financing, significantly enhances MSME competitiveness. However, challenges remain, particularly regarding the adoption of digital marketing technology and the optimization of distribution channels. This study provides strategic recommendations to improve the marketing effectiveness of MSME products, especially through the enhancement of STP and 4P strategies. By implementing the appropriate marketing approaches, Viriya Crispy Fish is expected to become more competitive, increase market penetration, and achieve sustainable growth. Additionally, this study offers insights into how Polri can continue to act as a facilitator for MSME development through more focused and innovative programs.